The effect of amino acid analogues on larval growth and survival of the olive fruit fly Bαctrocerα oleαe (Diptera: Tephritidae) - Manoukas Α. G. (ENTOMOLOGIA HELLENICA, 2000)
The effects of eight amino acid analogues [L-canavanine, D-cycloserine, allylglycine, L-glutamic acid-A-hydrazide, DL-ethionine, L-,-3,4 dihydroxyphenylalanine (L-DOPA), DL-,-3,4 dihydroxyphenyl-alanine (DL-DOPA) and thiaproline] added to an artificial diet on egg hatching, larval survival, larval weight, pupal weight and adult emergence of the olive fruit fly, Bactrocera oleae (Gmelin) (Diptera: Tephritidae) were investigated. Larval survival and weight were significantly decreased by all amino acid analogues tested. Pupal weight and adult emergence was depressed by L-canavanine, D-cycloserine, L-DOPA, DL-DOPA and allyl-glycine. Of all amino acid analogues tested only L-canavanine inhibited hatching of the eggs. The depression of the parameters affected was increased by increasing the concentration of each analogue tested. The larvae of most experimental diets took longer to pupate than those of the control.